Pengenalan Black Soldier Fly (BSF) Maggot sebagai Upaya Pengolahan Sampah Organik Rumah Tangga (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Population growth and changing consumption patterns have led to a continuous increase in waste generation, with household organic waste being the dominant component in Bantul Regency. Low levels of public knowledge and awareness regarding waste management are also contributing factors. One environmentally friendly alternative for organic waste management is the use of Black Soldier Fly (BSF) larvae, which have high bioconversion capabilities. This community service activity aims to increase the knowledge of housewives in managing household organic waste using BSF maggots. The activity was carried out in RT 01, Mojosari Hamlet, Baturetno Village, Banguntapan District, Bantul Regency, involving 20 participants. The implementation method included a site survey, material delivery, an introduction to the life cycle and benefits of BSF maggots, an explanation of waste sorting, maggot feeding, and post-activity observations. However, limitations in maggot maintenance techniques persisted, requiring ongoing mentoring. This activity contributes to reducing waste generation at its source and supports sustainable household waste management based on community participation.